Antimicrobial stewardship programs in acute-care hospitals: A multicenter assessment of structure, process, and outcome indicators in Italy and Spain - Giuseppina Lo Moro; Noemi Marengo; Alessandro Mara; José Ramón Paño Pardo; Sergi Hernandez; Ester Fusté; Miquel Pujol; Carla Maria Zotti; Enric Limón; Costanza Vicentini (Elsevier, 2024)
Background: Antimicrobial stewardship (AMS) programs have been differently implemented across Europe. This study primarily aimed to compare AMS in two European regions. Secondarily, the study explored the COVID-19 pandemic impact on surrogate outcome indicators of AMS. Methods: A retrospective observational study was conducted in Piedmont (Italy) and Catalonia (Spain). AMS programs were compared through structure and process indicators in 2021. Changes in surrogate outcome indicators (antimicrobial usage; alcohol-based sanitizer consumption; antimicrobial resistance, AMR) from 2017 to 2021 described the pandemic impact. Results: Seventy-eight facilities provided structure and process indicators. Catalonia showed better structure scores (p < 0.001) and less dispersion in both indicators. The greatest areas to improve were accountability (Piedmont) and diversification of strategies (Catalonia). Overall, the regions reported consistent changes in outcome indicators. Antimicrobial usage decreased in 2020, returning to near-pre-pandemic levels in 2021. Alcohol-based sanitizer consumption surged in 2020, then dipped remaining above pre-pandemic levels. AMR trends were minimally affected. Conclusions: The centralized approach of Catalonia ensured consistent attainment of quality objectives across all facilities, but it may limit facility-specific strategies. In Piedmont, accountability remain one of the most critical factors as in previous years. The pandemic did not substantially disrupt surrogate outcome measures of AMS. However, the data on AMR suggest that maintaining vigilance against this issue remains paramount.